The Relationship Between Screen Time and Symptom Severity in Children with ADHD during COVID-19 Lockdown - Sriwaranun T. (2023)
Objectives: To investigate the relationship between screen time and symptom severity in children with ADHD during the COVID-19 lockdown. Methods: Caregivers of children with ADHD aged 7 to 16 years completed the screen time questionnaire and ADHD rating scales of the SNAP-IV-Thai version during and after the COVID-19 lockdown. The correlation between screen time and ADHD scores was assessed. Results: Of the 90 children, aged 11.31 ± 2.29 years, enrolled, 74.4% were male, 64.4% were in primary school, and 73% had electronic screens in their bedrooms. After adjusting with other factors, recreational screen time, both on weekdays and on weekend days, were positively correlated with ADHD scores (both inattention and hyperactive/impulsive scores). Studying screen time, on the other hand, was not associated with ADHD symptom severity. Compared to during the lockdown, studying screen time decreased after the lockdown, but recreational screen time and ADHD scores were not changed. Conclusion: Increasing recreational screen time was associated with worsening ADHD symptoms.